Dynamic analysis of aboveground open-top steel tanks subjected to wind loading. (1st November 2019) - Chiang, Yen-Chen; Guzey, Sukru
Highlights: Dynamic effect of storage tanks under wind loading are investigated. Natural vibration frequency of empty tanks were reported. Time step limit for explicit dynamic analyses was reported. Result of explicit dynamic analysis and static GNIA was compared. Resonance effect of empty tanks under wind load was found to not be significant. Abstract: Aboveground steel tanks are prone to buckle under wind loading if they are empty. Geometrically nonlinear explicit dynamic analysis of empty open-top tanks subjected to wind loading are conducted using finite element analysis (FEA). Tanks with five different height to diameter aspect ratios, 4.0, 2.0, 1.0, 0.4, and 0.2, are adopted. Tanks are subjected to a gust of wind which fluctuates in magnitude over time to investigate whether a minor fluctuation, 10% of the average pressure, will trigger resonant behavior. Tanks with geometrical imperfections are also investigated using both dynamic analysis and static geometrically nonlinear analysis including imperfection (GNIA). It is found that, no matter if the tank does or does not have geometrical imperfections, resonance is not observed. Thus, a static analysis may be adequate for a practical tank design. The natural vibration frequencies of empty open-top tanks are studied as well, and comparisons with theoretical solutions and FEA results from the literature are presented. The effective modal mass is discussed to investigate the dynamic characteristics of the tanks examined. Insights for conducting an explicit dynamic analysis, including converged mesh size and time step limits, are also presented.